Avifaunal disarray due to a single despotic species. Issue 12 (11th September 2013) - Maron, Martine; Grey, Merilyn J.; Catterall, Carla P.; Major, Richard E.; Oliver, Damon L.; Clarke, Michael F.; Loyn, Richard H.; Mac Nally, Ralph; Davidson, Ian; Thomson, James R.
Abstract: Aim: Reports of profound changes in species assemblages brought about by the influence of strongly interacting species are increasingly common. Where these strong interactors are sensitive to anthropogenic habitat changes, relatively small alterations in the environment can result in large and pervasive shifts in assemblages. We review the evidence for widespread assemblage‐level phase shifts across eastern Australia, triggered partly by anthropogenic habitat alteration and mediated by a native, despotic bird: the noisy miner Manorina melanocephala . Location: Eastern Australia. Methods: Based on the literature, we developed conceptual models of factors affecting site occupancy by, and ecosystem‐level effects of, the noisy miner. We also analysed recent trends in the reporting rate of the noisy miner across its range. Results: Individuals of this species cooperate to aggressively exclude almost all smaller bird species from the areas they occupy. The noisy miner is advantaged by habitat fragmentation and structural simplification—habitat changes that facilitate detection and interception of potential competitors by miners. We report that the species is increasingly prevalent, particularly close to forest and woodland edges. Such edges have mainly been created by human land use. The evidence we reviewed showed: (1) strong causal links between the noisy miner and depressed richness and abundance of smaller birds, particularly nectarivores and insectivores; (2) moderate evidence of a positive association with larger bird species; (3) reduced tree condition stemming from impaired control of insect herbivore populations by smaller insectivores; and (4) a plausible negative effect on plant reproduction through reduced tree condition, altered pollination services and altered seed dispersal. Main conclusions: This is the first synthesis to document the causes and likely ecological consequences of increasingly prevalent phase shifts catalysed by a despotic species on ecosystems at very large spatial scales (> 1 million km 2 ). Native species affected by human activities can become agents that induce ecological dysfunction.